Misreporting of Results of Research in Psychiatry. (16th April 2021) - Bowcut, Jana; Levi, Linda; Livnah, Ortal; Ross, Joseph S; Knable, Michael; Davidson, Michael; Davis, John M; Weiser, Mark
Abstract: Few studies address publication and outcome reporting biases of randomized controlled trials (RCTs) in psychiatry. The objective of this study was to determine publication and outcome reporting bias in RCTs funded by the Stanley Medical Research Institute (SMRI), a U.S. based, non-profit organization funding RCTs in schizophrenia and bipolar disorder. We identified all RCTs ( n = 280) funded by SMRI between 2000 and 2011, and using non-public, final study reports and published manuscripts, we classified the results as positive or negative in terms of the drug compared to placebo. Design, outcome measures and statistical methods specified in the original protocol were compared to the published manuscript. Of 280 RCTs funded by SMRI between 2000 and 2011, at the time of this writing, three RCTs were ongoing and 39 were not performed. Among the 238 completed RCTs, 86 (36.1%) reported positive and 152 (63.9%) reported negative results: 86% (74/86) of those with positive findings were published in contrast to 53% (80/152) of those with negative findings ( P < .001). In 70% of the manuscripts published, there were major discrepancies between the published manuscript and the original RCT protocol (change in the primary outcome measure or statistics, change in a number of patient groups, 25% or more reduction in sample size). We conclude that publication bias and outcome reporting bias is common in papers reporting RCTs in schizophrenia and bipolar disorder. These data have major implications regarding the validity of the reports of clinical trials published in the literature.